(untitled) (Emancipação, 2024)
The article aims to investigate how the COVID-19 pandemic created a new dynamic in prisons and how this impacted the lives of women incarcerated in the Hildebrando de Souza Public Prison (CPHSPG), in Ponta Grossa (PR), under the bias the implementation of Human Rights and through an intersectional gender approach. To this end, we used the mixed method (quanti-qualitative) and semi-structured interviews to collect data, with field research carried out at CPHSPG. The concern with the topic arises from the fact that mass incarceration has affected women in the last two decades, in Brazil and around the world. However, the topic is still invisible, with a lack of data and a lack of attention to the specific needs of these women. In this already fragile scenario, COVID-19 emerged. As a result, we concluded that the pandemic impacted the lives of those in custody at CPHSPG, with the absence of in-person visits; the suspension of “bags” and the lack of hygiene and food items; the absence of in-person inspections; and hearings via videoconference. These facts, combined with the CPHSPG’s small health team, the failure to allocate specific funds to combat COVID-19 and the absence of structural modifications, increased the vulnerability of prisoners and made the prison experience more painful.